Quality changes during storage in Thai indigenous leafy vegetable, Liang leaves (Gnetum gnemon var. tenerum) after different preparation methods - Siripongvutikorn, Sunisa; Usawakesmanee, Worapong; Pisuchpen, Supachai; Khatcharin, Nicha; Rujirapong, Chanonkarn (Italian Journal of Food Science, 2023)
Liang or Gnetum gnemon var. tenerum, an indigenous southern vegetable has recently attracted increasing interest due to its high nutritional value, creamy taste and lack of smell. The leaves with or without stem are washed with chlorinated water at 100 ppm for 15 min, stored at 4°C and investigated for physiochemical, chemical and sensory evaluations over time. Total phenolic and flavonoid contents were higher in treatments with stems (P < 0.05). Washing significantly increased moisture content and water activity (aw) in all treatments (P < 0.05). In addition, washing resulted in significantly higher DPPH and ABTS activity (P < 0.05). However, washing and stem detachment had no effect on sensory and physicochemical qualities. The sensory score of the 8-days stored sample was comparable to the fresh one (Day 0).